2017
DOI: 10.20883/pielpol.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Pielęgniarstwo – zawód szczególnie narażony na stres i wypalenie. Wybrane założenia teoretyczne i wstępne doniesienie z badań – część I

Abstract: Cel. Prezentacja wybranych założeń teoretycznych w zakresie wypalenia zawodowego oraz analiza wstępna wyników badań dotyczących subiektywnego odczuwania symptomów tego zjawiska wśród pielęgniarek. Materiał i metody. W badaniu wzięło udział 111 pielęgniarek zatrudnionych w poznańskim szpitalu. Wyniki zgromadzono na podstawie wypełnionych kwestionariuszy ankiety CBI. Wnioski. Pielęgniarki doświadczają niepokojących symptomów, mogących świadczyć o zmęczeniu, wyczerpaniu fi zycznym lub emocjonalnym, zarówno w aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The vast majority of respondents, as much as 79.9%, declared greater mental fatigue. Similar results were obtained by Nowakowska et al [21], in which 65% of nurses declared their work as emotionally exhausting. In the Mróz [23] study, emotional tension is consistent with the overloaded type, and negative correlation in functioning with unambitious type.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The vast majority of respondents, as much as 79.9%, declared greater mental fatigue. Similar results were obtained by Nowakowska et al [21], in which 65% of nurses declared their work as emotionally exhausting. In the Mróz [23] study, emotional tension is consistent with the overloaded type, and negative correlation in functioning with unambitious type.…”
Section: Discussionsupporting
confidence: 89%
“…Based on our own results, it was found that while caring for a patient with a diagnosed fetal defect, almost half of the midwives surveyed declared a deterioration in physical well-being. Nowakowska et al [21] in her research presents similar results. 39% of nurses participating in the survey complain of physical exhaustion during work.…”
Section: Discussionsupporting
confidence: 69%
“…However, the nature of these emotions significantly affects the physical and mental health of nurses. Too much emotional involvement may contribute to increasing the feeling of negative emotions, contribute to an increase in stress, and lead to occupational burnout [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that are most disturbing in the workplace, in a study by Rosinchuk et al [15], almost one in four respondents included bureaucracy and being saddled with duties incompatible with competence, as well as a small staff and a bad atmosphere at work. In a study by Nowakowska et al [52] conducted using the Copenhagen Burnout Inventory (CBI) survey questionnaire, nurses rated the workrelated area more pejoratively than the patient contact area. In a subsequent report, the same author presents additional findings, indicating that the education one has and the unit on which nurses work affect the incidence of job burnout, and that job burnout can adversely affect the performance of professional duties and relationships with family.…”
Section: Professional Burnout Of Nursing Staffmentioning
confidence: 99%